Determinants of Banking Financial Performance in Indonesia: An Empirical Analysis of Financial Statements - Sufiani, Muyassaroh Faizzatus; Sani, Ageng Asmara (BanKu: Jurnal Perbankan dan Keuangan, 2025)
Working in Progress